The effects of team co-location and reduced crewing on team communication characteristics. (November 2019) - Roberts, Aaron P.J.; Stanton, Neville A.; Fay, Daniel T.; Pope, Kiome A.
Abstract: The manner in which control rooms are configured can impact the flow of information between command teams. Previous research revealed bottlenecks of communications between the Sonar Controller (SOC) and the Operations Officer (OPSO) in submarine control rooms. One way to relieve such bottlenecks is to co-locate operators reliant on one another for task relevant information. The aim of the current studies was to use multiple command teams to empirically examine a novel submarine control room configuration and a reduced crew size in comparison to a baseline of contemporary operations to see if such bottlenecks could be removed. Ten teams performed high and low demand Dived Tracking (DT) scenarios in a simulated submarine control room. Activities and communications of the teams were recorded and quantified using the Event Analysis of Systemic Teamwork (EAST) method affording statistical comparisons with a baseline condition of contemporary operations. The findings showed that the co-location of operators relieved the bottleneck of communications between the SOC and the OPSO. Although overall communications increased, this was more balanced across the team and was more adaptive to scenario demand. This was coupled with a significant increase in task completion, even with a reduced crew size, suggesting greater efficiency and productivity. Future research should seek to validate the changes observed with objective measures of task performance. Highlights: The performance of submarine command teamsin different control room configurations with reduced crew sizes was assessed. The co-location of operators improved information flow, information structure and overall productivity. The co-location configuration optimised performance to the extent that two operators could be removed from the command team. The spare cognitive capacity of operators in the command teams significantly increased in the co-location configuration.